SEVERAL TYPES OF ENGLISH ARTICLE FOUND IN THE NOVEL LIGHTNING AND ITS TRANSLATION KILAT MENYAMBAR - Nila Mayasari; Nurhasanah Nurhasanah (Universitas Mahaputra Muhammad Yamin, 2019)
Translation is replacing text material in the source language with equivalent text language in the target language, and the meaning of other translations mentions translating the meaning of a text into another language according to what was intended by the author. In translation activities, an interpreter returns the contents of a text in another language. This submission is not just a replacement activity, because translation in this case carries out new communication activities through the results of existing communication activities (ie in the form of text), but by paying attention to social aspects when the new text will be read or communicated. In translating concepts and translation procedures, it is necessary to produce appropriate and acceptable translations. This study aims to find out the types of translations of English articles into Indonesian and also through the translation procedures from the Lightning by Danielle Steel novel and thetranslation of the Flash Enchanting. The data obtained are explained using the descriptive method of pliers given by Sudaryanto (1993). Theories about the types of English articles were given by Catford (1965; Cyssco (2000); Warner (1985) and Alter (1991) and theories regarding translation were given by catford (1965); Pinchuck (1977); and Larson (1988 ) The author in this study found types of article translations such as zero article, definite article, indefinite article, and partitive article, English from discussing sources to target languages, namely from English to Indonesian, and also researchers found translation procedures such as literal, transposition , modulation.